The Moral Value Analysis As Reflected in Novel “ Akeelah And The Bee” - Rizqi Claudia Wardani; Dewi Purwati (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
In this study, the writer chose the “Akeelah and the Bee” novel to be analyzed the important of moral values as a part of our life. For that reason the writer wants to investigate and doing research in the library. The formulation of problem in this research is “ What are the moral values as reflected in the novel “ Akeelah and the Bee”. The methodology of this study is qualitative study. it is means that it does not need statistic approach to explore the material. The primary data is scrip from the movie “Akeelah and the Bee”. The secondary data is taken from many literary books and some relevant materials to support and complete the primary data sources. The result of this study is there are some moral values in the “Akeelah and the Bee” novel. They are love and affection, sacrifice, sorry and Apologize, optimism, honesty, kind and friendly, hardworker, ambition, not easily to surrender, firm, serious and discipline, and helper.